Agronomic association of Vrn, Ppd, Rht genes and identified QTLs under contrasting tillage conditions in wheat - Yadav, Rajbir; Sagar, Vidya; Jain, Neelu; Gaikwad, KB (Journal of Cereal Research, 2014)
Improved varieties have played important role in higher yield realization in tandem with improved management practices. Conservation agriculture as an improved environment for higher production requires adaptive variety to further the yield gain. Higher effect of environment along with equally important GÃ—E makes selection on the basis of phenotypic traits more risky and less rewarding. Molecular markers with lesser effect of environment and independent of stage and condition for their expression present attractive option to breeders to improve selection efficiency. Various Vrn, Ppd and Rht genes along with number of QTLs identified by researchers have adaptive role in wheat. Genotypes showing differential adaptiveness were grown under three contrasting environments generated by different tillage-sowing methods. Gene specific markers were scored and genotypes were grouped as per markers profile. Grouping on the basis of markers was correlated with phenotypic grouping, though not so strongly, under different environments, picking conservation agriculture adaptive genotypes under one node and genotypes adapted for conventional tillage in another node. Contrasting pool created by identified QTLs under its adaptive growing environment does not show any differentiating ability and therefore requires further validation before use in breeding programme.